Efek Keragaman Produk dan Harga Produk terhadap Impulse Buying - Arya, Gede Reydi Wahyu; Telagawathi, Ni Luh Wayan Sayang (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aimed at examining: (1) the effect of product variety and price effect toward impulse buying at Matahari Duta Plaza Bali, (2) the effect of product variety toward impulse buying at Matahari Duta Plaza Bali, (3) the effect of price toward impulse buying at Matahari Duta Plaza Bali. The research method used in this study was causal quantitative meanwhile purposive sampling as the technique to collect the sample. The instrument that used to collect the data was a questionnaire consisted of 13 items. The result obtained was then analyzed by using multiple linear regression analysis. The data was obtained from the respondents who ever been done impulse buying at Matahari Duta Plaza Bali. The result of the study showed that: (1) product variety and price have a significance and simultaneous effect on impulse buying at Matahari Duta Plaza Bali at 65,2% and 34,8% influences by other factors outside the model, (2) product variety has significance partially effect on impulse buying at 32,3%, and (3) price has significance partially effect on impulse buying at 17,1%.